Manajemen Pengelolaan Bukti Digital Untuk Meningkatkan Aksesibilitas Pada Masa Pandemi Covid-19 - Moch Bagoes Pakarti; Dhomas Hatta Fudholi; Yudi Prayudi (Jurnal Ilmiah SINUS, 2021)
Covid-19 has a major impact on human life, including the process of managing digital evidence. Management of digital evidence requires special handling that can store and maintain the integrity of digital evidence. The current problem is there is no concept of storing digital evidence that can be accessed online in wider accessibility. Online digital evidence management is proposed as a solution to solve this problem. This concept is in the form of an online digital evidence management system that can be accessed anywhere and anytime using MD5 and SHA1 hash functions in order to maintain the properties of digital evidence so that it can be legally accepted. The problems with digital evidence management require a Management System for Digital Evidence that is suitable for application in Digital Forensics Laboratory. This research had successfully implemented the concept of online chain of custody. It is expected, with the concept of Online Digital Evidence Management, this digital evidence control and all activities related to it can be maintained and well documented. Moreover, it can reach a wider area accessed anywhere and any time and reduce the spread of Covid-19.